Advanced Bearing System for Ultra Precision Plastic Electronics Production Systems - Zhao, Gang (Cranfield University, 2014)
The aims of this MSc research project are to investigate the application of aluminium for the main components of an ultra-precision spindle defined for use in R2R production systems and to produce a reel to reel rotary aluminium hydrostatic bearing system of high accuracy to meet the demand of manufacturing the flexible displays with an effective production capability for this special kind of film-based product. The original concept design was already finished to manufacture the bearing components and the objective of this project was to test the functionality of this new hydrostatic bearing system. Firstly, theoretical were performed to work out the output responses, including temperature rise, flow rate, load capacity etc., of the hydrostatic bearing system under different input design parameters, including supply pressure, fluid viscosity, the rotational speed etc. Then ANSYS software was used to build a FEA model to simulate the actual working conditions of the hydrostatic bearing system and to obtain the theoretical output parameters, especially the deflection conditions of the bearing shaft. Finally the experimental validation tests were conducted to verify the actual output responses to check correlation with the modelled results.
Keywords: R2R production systems; hydrostatic bearing systems; input parameters; output responses; FEA modelling; deflection conditions of the deflection conditions of thedeflection conditions of the bearing shaft